The Effects of Financial Inclusion on Non-Performing Bank Loans in Indonesian (The Period of 2013-2024) - Ramadhany, Diwa Artha Ramadhany; Kaluge, David (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Financial inclusion in Indonesia has significantly increased, reaching 85.1% in 2022. However, only 51% of the population accesses formal financial services, with the majority of unbanked people engaged in the MSME sector. While MSMEs are the backbone of the economy, integrating unbanked people into the formal financial system may escalate credit risks reflected in Non-Performing Loans (NPL). This study analyzes the impact of financial inclusion on NPL across Indonesia's provinces from 2013 to 2024 using robust regression with Least Trimmed Squares (LTS) estimation to address outliers. The results show that financial service branch office (Access) and MSME credit (Usage) contribute positively to NPL. Macroeconomic factors such as GRDP and unemployment are also significant while inflation does not significantly affect NPL. This study provides insights to enhance financial literacy and manage credit risks, supporting sustainable financial inclusion growth.